Reaching into the basket of doom: Learning outcomes, discourse and information literacy. (June 2023) - Hicks, Alison; Lloyd, Annemaree
Learning outcomes form a type of arrangement that holds the practice of information literacy within higher education in place. This paper employs the theory of practice architectures and a discourse analytical approach to examine the learning goals of five recent English-language models of information literacy. Analysis suggests that the practice of information literacy within higher education is composed of 12 common dimensions, which can be grouped into two categories, Mapping and Applying. The Mapping category encompasses learning outcomes that introduce the learner to accepted ways of knowing or what is valued by and how things work within higher education. The Applying category encompasses learning outcomes that encourage the learner to implement or integrate ideas into their own practice, including to their own questions, to themselves or to their experience. Revealing what is prioritised as well as what is less valued within the field at the present time, these findings also raise questions about supposed epistemological differences between models, the influence of research, and the language employed within these documents. This paper represents the third and final piece of work in a research programme that is interrogating the epistemological premises and discourses of information literacy within higher education.